A polysulfobetaine hydrogel for immobilization of a glucose-binding protein. Issue 87 (5th September 2016) - Kasák, Peter; Mosnáček, Jaroslav; Danko, Martin; Krupa, Igor; Hloušková, Gabriela; Chorvát, Dušan; Koukaki, Marina; Karamanou, Spyridoula; Economou, Anastassios; Lacík, Igor
Abstract : A hydrogel based on sulfobetaine methacrylate monomer and crosslinker was investigated as a potential material for fluorescent glucose biosensor applications. Abstract : A hydrogel based on sulfobetaine methacrylate monomer N -(methacryloyloxyethyl)- N, N -dimethyl- N -(3-sulfopropyl)ammonium betaine and N, N -bis(methacryloyloxyethyl)- N -methyl- N -(3-sulfopropyl)ammonium betaine used as a crosslinker was investigated as a potential material for biosensor applications. The glucose diffusion coefficient of 1.2 × 10 −10 m 2 s −1 was determined from the glucose release experiment. Inverse size-exclusion chromatography was performed to determine the molecular weight cut-off of the hydrogel to be 8 kDa with respect to pullulans that corresponds to a viscosity radius of 2.1 nm. The narrow pore-size distribution suggests that using the sulfobetaine crosslinker suppresses the composition drift and results in a homogeneous hydrogel network. Furthermore, a glucose biosensor construct comprising the periplasmic glucose-binding protein of Escherichia coli fused to cyan and yellow fluorescent proteins was effectively entrapped in the hydrogel exhibiting no leakage for at least 7 days. The glucose-binding protein showed stability of its secondary structure and sensitivity to glucose as assessed by circular dichroism and Förster (fluorescence) resonance energy transfer measurements under physiological conditions and a physiological range of glucose concentration, respectively.